2021
DOI: 10.1029/2020jd034183
|View full text |Cite
|
Sign up to set email alerts
|

Variation of Snow Mass in a Regional Climate Model Downscaling Simulation Covering the Tianshan Mountains, Central Asia

Abstract: The seasonal snowpack plays an essential role in the water resources budget of the global mountainous area and provides freshwater supply for over 1/6 of the world's population (Barnett et al., 2005;, which has a profound effect on the food production of irrigated agriculture and snowmelt runoff regimes in the snow-dominated basin (Qin et al., 2020). It also strongly affects regional climate system, alpine phenology, and biogeochemical processes through regulation of the land-atmospheric exchanges of water and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 122 publications
(241 reference statements)
0
15
0
Order By: Relevance
“…The uncertainty of the snow simulation in the RCMs was influenced by the quality of the simulated precipitation and temperature (Liu et al ., 2019; Wrzesien et al ., 2019). An underestimation in the total precipitation during the cold season was revealed in the low altitude regions of the western and southern Tianshan Mountains, and the intersection between the northern and eastern Tianshan Mountains (Yang et al ., 2021). On the other hand, possible reasons of the overestimation in snow depth at mid‐high altitude regions were mainly caused by the severely overestimated precipitation of the model and the undercatch of the snowfall in the gauge observations (Bonekamp et al ., 2018).…”
Section: Discussionmentioning
confidence: 99%
“…The uncertainty of the snow simulation in the RCMs was influenced by the quality of the simulated precipitation and temperature (Liu et al ., 2019; Wrzesien et al ., 2019). An underestimation in the total precipitation during the cold season was revealed in the low altitude regions of the western and southern Tianshan Mountains, and the intersection between the northern and eastern Tianshan Mountains (Yang et al ., 2021). On the other hand, possible reasons of the overestimation in snow depth at mid‐high altitude regions were mainly caused by the severely overestimated precipitation of the model and the undercatch of the snowfall in the gauge observations (Bonekamp et al ., 2018).…”
Section: Discussionmentioning
confidence: 99%
“…The LUCs in the ECOCLIMP II dataset were divided into 573 ecosystems according to the land cover with climate maps (Champeaux et al., 2005). Due to the outdated land‐use cover data, the ECOCLIMAP could not correctly reveal the real land cover status (He, Luo, et al., 2021; T. Yang et al., 2021). The previous comparison indicated that the Climate Change Initiative Land cover dataset (CCI‐LC) from ESA (with high overall accuracy) could better exhibit a homogeneous land cover change in China, particularly in the farming zone of the northern part (Yang et al., 2017).…”
Section: Methodsmentioning
confidence: 99%
“…The LUCs in the ECOCLIMP II dataset were divided into 573 ecosystems according to the land cover with climate maps (Champeaux et al, 2005). Due to the outdated land-use cover data, the ECOCLIMAP could not correctly reveal the real land cover status T. Yang et al, 2021).…”
Section: Description Of the Land Surface Conditionsmentioning
confidence: 99%
See 2 more Smart Citations